2017
DOI: 10.7150/jca.21476
|View full text |Cite
|
Sign up to set email alerts
|

Local surgical excision versus endoscopic resection for rectal carcinoid: A meta-analysis.

Abstract: Purpose: To date, there is not enough evidence concerning the optimal treatment strategy for early rectal carcinoids, we conducted a meta-analysis in order to determine the feasible local treatment for these selected patients.Methods: We searched the studies from the PubMed, Cochrane database, Medline, Ovid, SpringerLink, PMC and Embase between January 2007 and April 2017. Studies of local surgical excision compared with endoscopic resection for rectal carcinoids less than 20mm without adverse features were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…However, those between 10 and 20 mm in size remain controversial. Recent studies have shown oncological safety comparable to that of local surgical excision for lesions 20 mm or smaller in diameter without adverse features and treated with ER (20). In the present study, 80.9% of the tumors were less than 10 mm in size, whereas 19.1% of the tumors larger than 10 mm.…”
Section: Discussionsupporting
confidence: 59%
“…However, those between 10 and 20 mm in size remain controversial. Recent studies have shown oncological safety comparable to that of local surgical excision for lesions 20 mm or smaller in diameter without adverse features and treated with ER (20). In the present study, 80.9% of the tumors were less than 10 mm in size, whereas 19.1% of the tumors larger than 10 mm.…”
Section: Discussionsupporting
confidence: 59%
“…In traditional cognition, surgery is the best treatment for carcinoids, and the surgical method is selected according to the size of the carcinoid, depth of invasion, and lymph node metastasis [6,7]. At the same time, studies have shown that endoscopic treatment can have a better effect on carcinoids that measure less than 2 cm in diameter [8][9][10]. Small-probe endoscopic ultrasonography (EUS) is becoming increasingly widely used in endoscopy because of its simple operation and because it can provide references for the size, origin level, depth of invasion, surrounding lymph nodes, and blood vessels of the lesion, thus further guiding the resection of submucosal lesions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic appearance is a kind of information which can be easily assessed and available in most of the patients. Studies about endoscopy for rectal NET are actually not rare but most of them mainly focused on investigating the complete excision rates of different endoscopic or local resection methods [5][6][7]. Few studies investigated the capability of endoscopic appearance of rectal NET to evaluate its malignant behavior.…”
Section: Introductionmentioning
confidence: 99%